Competitiveness of exporting companies in Mantaro Valley of sector clothing industry - Vilca Rodriguez, Roy River (2020)
The research soughtvto determine the competitive level of export companies  in the Valle del Mantaro - Clthing inductry sector. The study is of a descriptive and cross-sectional nature. The data was obtained through a survey and personal interview based on the BID competitive map. Concluding with a general competitiveness of 52% that indicates a low competitive level.